Production, physicochemical, microbiological and nutritional analysis of the liquor obtained from the peelings of annas Comusus reinforced by the root extract of Mondia whitei harvested in Benin - KOUDORO, YAYA ALAIN (My University, 2022)
In Benin, Ananas Comosus co-products are often left in wild dumpsites for flies and mosquitoes and are a source of foul odour. The main objective of this study is to valorize the co-products of the Ananas Comosus processing industry through the formulation of the liquor reinforced with bioactive substances. To do this, the secondary metabolites of the Mondia whitei root were identified by staining and precipitation reactions specific to each metabolite. After the elaboration of the liquor, the organoleptic and physicochemical properties of this product were determined. The contents of phenolic compounds in the liquor were evaluated by spectrophotometric assay. The quantification of its mineral salt content was carried out by atomic absorption spectrophotometry. Finally, the microbiological quality of the formulated product was determined according to ISO standards. From the results obtained, it appears that the root of Mondia whitei is rich in secondary metabolites. The pH of the formulated liquor is 4.75 and its soluble solids content is 15°Brix. Total phenol concentrations; in flavonoids and in condensed tannins are respectively 11.31 mg GAE/mL; 15.07 μg QE/mL and 34.43 mg LeucE/mL. The resulting liquor is rich in mineral salts (P, K, Ca, Mg, Na, Fe and Mn); its alcohol content is 45%. From a microbiological point of view, it is free of any pathogenic germ and meets the normative requirements. From the sensory analysis, it is well appreciated by all the tasters (>73%).
Keywords: Ananas Comosus; secondary metabolites; liquor; analyses; Mondia whitei